Core-hole jumping between heavy atoms enabled by retardation - Hofierka, Jaroslav; Cederbaum, Lorenz S. (Physical review, 2024)
In interatomic Coulombic decay (ICD) an excited neutral atom or excited ion transfers its excess energy to ionize a neighboring atom. If the excitation or ionization involves valence electrons, the process is efficient (typically in the femtosecond regime), becomes more efficient the more neighbors are present, and often dominates all other relaxation processes. The situation changes when considering the excitation or ionization of core electrons. For light atoms, core-level ICD is inferior to Auger decay, but still a relevant relaxation pathway. For heavy atoms the excess energy is enormous and by consulting the usual asymptotic equation for the ICD rate one can only conclude the deep core-level ICD to be negligible. Retardation effects due to the finite speed of light strongly change the asymptotic behavior of the ICD rate, in particular for deep core levels. The impact of retardation is investigated in detail for deep core-level ICD. Several examples of heavy atoms undergoing ICD with heavy neighbors are explicitly studied and general conclusions are drawn.